Приближенный расчет энерговыделения и электрической эрозии электродов в высоковольтном сильноточном воздушном коммутаторе атмосферного давления - Баранов, Михаил Иванович; Рудаков, Сергей Валерьевич (НТУ "ХПИ", 2017)
Приведены результаты применения нового инженерного подхода к расчету тепловой энергии, выделяющейся в плазменном канале искрового разряда и на массивных металлических электродах высоковольтного сильноточного воздушного коммутатора (ВСВК) атмосферного давления, используемого в составе высоковольтной электрофизической установки (ВЭФУ) с мощным емкостным накопителем энергии (ЕНЭ). Полученные соотношения для определения указанной энергии позволяют выполнять расчетную оценку баланса электрической энергии в разрядной цепи ВЭФУ с ЕНЭ с учетом ее тепловых потерь в ВСВК. Показано, что на основе разработанного подхода может быть выполнен расчет электрической эрозии основных металлических электродов ВСВК. Получены новые расчетные выражения для нахождения глубины одиночного кратера разрушения на металлических электродах ВСВК и массы металла, выбрасываемой искрой из электродов исследуемого коммутатора за один разряд ЕНЭ установки.

On the basis of new engineering approach the results of calculation estimation of excretions energy and electric erosion of massive basic metallic electrodes are resulted in probed HVCAS. New correlations are obtained for the approximate calculation of thermal energy, selected in an impulsive air spark and on the workings surfaces of anode and cathode of HVCAS. It is entered and a new electrophysics concept, touching equivalent active resistance of impulsive air spark, is mathematically certain. New formulas are obtained for the approximate calculation of most depth of single round crater of destruction on the workings surfaces of basic metallic electrodes of HVCAS, and also mass of metal, thrown out magnetic pressure from this crater of destruction on the electrodes of switch for one electric discharge through them powerful CSE HVES. It is shown that the radius of the indicated single crater of destruction is approximately equal to the maximal radius of plasma channel of a spark discharge between a cathode and anode of HVCAS. The executed high-current experiments in the bit chain of HVES with powerful CSE validated row of the got and in-use calculation correlations for the estimation of energy dissipation and electric erosion of metallic electrodes in examined HVCAS.
An approximate calculation of energy dissipation and electric erosion of electrodes in the high-voltage high-current air switch of atmospheric pressure
Keywords: емкостный накопитель энергии; ЕНЭ; высоковольтная импульсная техника; ВИТ; большой импульсный ток; БИТ; двухэлектродная система